The movement of “Drinking tea instead of the alcohol” as the health promotion - Lu, Fang Tsuang; Lo, Shu-Fen (Technium Social Sciences Journal, 2023)
Due to the colonization by Japan in 1895 and implemented the system of public of tobacco and alcohol, destroyed the aboriginal original traditional custom. The public alcohol system brought the alcohol abuse to all aboriginals in Taiwan which caused a lot serious healthy problem, no working ability, drunk driving accident and increasing in domestic violence. The author organized the promote team and hold more than 300 times of health education in 5 aboriginal townships. The second stage, the promote team found there should be a local strength long lasting and continuously to promote this movement. Therefore, the “tea club” were set up one after another. This was the key point of success. This movement has been promoted for 12 years and still going on. At that time, the head of the Hualien County Health Bureau affirmed that this was a pioneering work in the public health sector.